The Impact of Electricity Shortages on Firm Productivity : Evidence from Pakistan - Grainger, Corbett A.; Zhang, Fan (World Bank, Washington, DC, 2017)
Power shortages present a significant challenge to manufacturers, who rely on power as a key input to production. In Pakistan, power shortages are commonplace, but empirical evidence on the impact of shortages is still lacking. Using a survey of 4,500 manufacturing firms for the year 2010-11, this paper estimates the impact of electricity shortages on firm productivity in Pakistan. The analysis finds that a 10 percent increase in the duration of outages on average leads to a 0.14 percent decrease in a firm's total revenue and a 0.36 percent decrease in the value added, all else being equal. There is heterogeneity in the impacts of shortages across sectors: the industries that are most energy-intensive, such as manufacturers of metal, wood, and paper, are affected the most severely by shortages.